2010
DOI: 10.1086/657410
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Vaccine‐Derived Poliovirus from Patients with Acute Flaccid Paralysis in China: Current Immunization Strategy Effectively Prevented Its Sustained Transmission

Abstract: In China, 5 patients with acute flaccid paralysis (AFP) associated with type 2 vaccine-derived poliovirus (VDPV) were identified by an AFP surveillance system from 1996 through 2009. A maximum-likelihood tree shows that all 5 Chinese VDPVs were independent. These 5 VDPVs were 100-216 d old according to the number of synonymous substitutions per synonymous site and 176-292 d old according to the number of substitutions per site. This result indicates limited virus replication since the administration of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…In this study, none of the viruses of genomic patterns A and B (which have an unmodified Sabin 2 5′UTR sequence) was neurovirulent, whereas almost all the viruses of genomic patterns C and D caused disease in mice, confirming the crucial importance of the 5′UTR in the loss of attenuation of Sabin 2-derived recombinants. These results are consistent with observations that the 5′UTR of pathogenic type 2 cVDPVs is modified by mutations affecting the adenine nucleotide in position 481, which is known to be a major determinant of attenuation of Sabin 2, or by recombination with other EV-Cs15171819213747484950. The key role of the 5′UTR in the pathogenicity of PVs has also been demonstrated for serotypes 1 and 338515253.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, none of the viruses of genomic patterns A and B (which have an unmodified Sabin 2 5′UTR sequence) was neurovirulent, whereas almost all the viruses of genomic patterns C and D caused disease in mice, confirming the crucial importance of the 5′UTR in the loss of attenuation of Sabin 2-derived recombinants. These results are consistent with observations that the 5′UTR of pathogenic type 2 cVDPVs is modified by mutations affecting the adenine nucleotide in position 481, which is known to be a major determinant of attenuation of Sabin 2, or by recombination with other EV-Cs15171819213747484950. The key role of the 5′UTR in the pathogenicity of PVs has also been demonstrated for serotypes 1 and 338515253.…”
Section: Discussionsupporting
confidence: 91%
“…Such mutations are probably necessary for the increase in fitness required for field cVDPVs to emerge as pathogenic strains. In particular, residue 143 of VP1, which is known to be a determinant of attenuation37, is generally found to be mutated in cVDPVs isolated from patients15171819214950. This result is consistent with the finding that most pathogenic cVDPVs circulate for months before causing poliomyelitis cases810.…”
Section: Discussionsupporting
confidence: 82%
“…In order to elucidate the divergence and evolution of the Sichuan type 2 cVDPVs, the VP1 sequences of the following viruses were analyzed: 5 Sichuan type 2 cVDPV strains in this study, sporadic type 2 VDPV identified in China earlier (GenBank accession numbers AY948201 and HM107832-HM107835) (7,22), Egypt type 2 cVDPVs (GenBank accession numbers AF448782 and AF448783) (23), Madagascar type 2 cVDPVs (GenBank accession numbers AM084223 and AM084225) (24), and Nigeria type 2 cVDPVs (GenBank accession numbers JX274980, JX274985, JX275162, and JX275380) (9).…”
Section: Epidemiologic and Clinical Background Circulation Of Indigementioning
confidence: 99%
“…The Chinese immunization program is widely regarded to be one of the country's most successful public health endeavors under challenging conditions: (i) a very large population (estimated population, 1.336 billion in 2009; proportion of population aged Ͻ15 years, 18.5%; birth rate, 12.09‰; birth cohort, estimated at 16.46 million); (ii) high population density with an unbalanced distribution, average of 134 persons per square kilometer; eastern coastal area, Ͼ400 persons per square kilometer; central area, about 200 persons per square kilometer; western plateau area, Ͻ10 persons per square kilometer; and (iii) hard-to-reach populations in the mountainous area (32). Despite the challenging conditions, all Chinese children have the opportunity to receive vac-cination against these infectious diseases free of charge, and vaccine-preventable diseases targeted by the expanded program on immunization are at low levels of incidence overall.…”
mentioning
confidence: 99%